Pengaruh Pendampingan Diet Terhadap Kepatuhan Diet Dan Kadar Gula Darah Pada Penderita Diabetes Mellitus Di Wilayah Puskesmas Balowerti Kota Kediri - Puguh Santoso; Erna Susilowati (Akademi Keperawatan Dharma Husada Kediri, 2018)
Background: Diabetes (DM) is a disease caused by the body is not able to make or use insulin properly, this can lead to complications in the future and cause DM disease suffered more severe. The success of a treatment is determined by the DM patient's attitude toward the treatment. With the compliance of patients with DM then treatment will reach the optimal level, and the quality of health can still be felt. Controlled category of DM is also seen from the results of HbA1C levels, One method that can be used to improve adherence is by counseling dietary behavior. The purpose of the study to determine whether there is Influence Diet Facilitation To Diet Compliance In Diabetes Mellitus patients in Posyandu Elderly